Kleefstra syndrome and sleep disorders: An Italian case report - Ettore Caterino (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2023)
Kleefstra Syndrome (KS)is a rare genetic syndrome affecting approximately 1 in 200,000 individuals and is caused by either a deletion of the subtelomeric region of chromosome 9q (50%) or by a loss of function mutation in the Euchromatin Histone Methyl Transferase 1 (EHMT1) gene (50%). In this case report we analyze the case of an 8-year-old boy affected by KS from the parent's point of view. The focus of the report is the detailed narrative analysis of the parent's experience written directly by the mother and the complex intervention to reduce a severe sleep disturbance associated with the syndrome. A clinical assessment was carried out, focused on understanding the extent and frequency of the awakenings with a specific assessment questionnaire. The association of therapy with melatonine and trazodone was highly decisive and improved the well-being of the child and the family. The Author is carrying out further studies for the drafting of guidelines for sleep disorders in KS.